Arthroplasty Roundtable: Leg-Length Discrepancy After Hip Arthroplasty. Issue 4 (29th October 2021) - Creamer, Samantha; Johnson, Joshua R.; Davis, Christopher; Cloutier, Dagan
Abstract : The purpose of the Journal of Orthopaedics for Physician Assistants Roundtable discussion is to give orthopaedic physician assistants insight on how each participating editorial board member treats certain clinical scenarios in their current practice. For this Arthroplasty Roundtable, editorial board members with expertise in total joint replacement will discuss leg-length discrepancy after hip arthroplasty. Participants will share their knowledge and experience on the topic. The Roundtable discussion will start with a brief case presentation.